2020
DOI: 10.1096/fj.202000143rrr
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal vitamin D receptor signaling ameliorates dextran sulfate sodium‐induced colitis by suppressing necroptosis of intestinal epithelial cells

Abstract: Vitamin D status is closely related to inflammatory bowel disease (IBD), but the mechanism has not been fully elucidated. This study explored the effect of intestinal vitamin D signaling on necroptosis and the underlying mechanism in colitis. Serum 25(OH)D levels and the expression of necroptotic proteins were examined in patients with IBD. Colitis was induced in an intestinal‐specific hVDR transgenic model, and the gross manifestation, histological integrity, and intestinal barrier function were tested. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In addition, mice with VDR knockout spontaneously develop hepatic fibrosis as a consequence of intersecting VDR/Smad genomic pathways (31). In acute enteritis, VDR maintains intestinal epithelial integrity by inhibiting apoptosis and necroptosis (32,33). Therefore, we investigated whether VDR functions in intestinal fibrosis induced by repeated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mice with VDR knockout spontaneously develop hepatic fibrosis as a consequence of intersecting VDR/Smad genomic pathways (31). In acute enteritis, VDR maintains intestinal epithelial integrity by inhibiting apoptosis and necroptosis (32,33). Therefore, we investigated whether VDR functions in intestinal fibrosis induced by repeated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Does RIP3-mediated cell necroptosis play an important role in the pathogenesis of UC? Endogenous ligand/receptor signaling such as vitamin D/Vitamin D receptor (VDR) may inhibit RIP3-mediated necroptosis; Vitamin D and VDR signaling has been shown to have immune-protective effects on inflammatory bowel disease [ 41 ] and suppress necroptosis in intestinal epithelial cells by binding RIPK1/3 necrosomes [ 42 ]. In this study, we applied two RIP3 inhibitors—Nec-1 and GSK872.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported an inhibitory effect of the intestinal vitamin D signaling pathway on DSS-induced necroptosis colitis in IBD patients, 16 while another in-vitro experimental study reported that DSS-induced colonic mucosal damage was more severe in mice with vitamin D receptor (VDR) deletion of the colonic epithelium than in the control group. 17 Moreover, another study showed that vitamin D deficiency in experimental models caused colitis with clinical symptoms and severe colonic mucosal damage. 18 In our study, IL-17 expression in Group 2 (5% DSS alone) was significantly higher than in Group 1 (control), indicating that IL-17 expression increases in colitis conditions.…”
Section: Discussionmentioning
confidence: 99%